Hyperbaric oxygen preconditioning ameliorates blood-brain barrier damage induced by hypoxia through modulation of tight junction proteins in an in vitro model - Hao, Lei (Croat Med J, 2016)
AIM: To explore the effects of hyperbaric oxygen preconditioning (HBOP) on the permeability of blood-brain barrier (BBB) and expression of tight junction proteins under hypoxic conditions in vitro. METHODS: A BBB in vitro model was constructed using the hCMEC/D3 cell line and used when its trans-endothelial electrical resistance (TEER) reached 80-120 Ω · cm(2) (tested by Millicell-Electrical Resistance System). The cells were randomly divided into the control group cultured under normal conditions, the group cultured under hypoxic conditions (2%O(2)) for 24 h (hypoxia group), and the group first subjected to HBOP for 2 h and then to hypoxia (HBOP group). Occludin and ZO-1 expression were analyzed by immunofluorescence assay. RESULTS: Normal hCMEC/D3 was spindle-shaped and tightly integrated. TEER was significantly reduced in the hypoxia (P = 0.001) and HBOP group (P = 0.014) compared to control group, with a greater decrease in the hypoxia group. Occludin membranous expression was significantly decreased in the hypoxia group (P = 0.001) compared to the control group, but there was no change in the HBOP group. ZO-1 membranous expression was significantly decreased (P = 0.002) and cytoplasmic expression was significantly increased (P = 0.001) in the hypoxia group compared to the control group, although overall expression levels did not change. In the HBOP group, there was no significant change in ZO-1 expression compared to the control group. CONCLUSION: Hyperbaric oxygen preconditioning protected the integrity of BBB in an in vitro model through modulation of occludin and ZO-1 expression under hypoxic conditions.